2021
DOI: 10.3389/fneur.2021.713520
|View full text |Cite
|
Sign up to set email alerts
|

Altered Coupling Between Resting-State Cerebral Blood Flow and Functional Connectivity Strength in Cervical Spondylotic Myelopathy Patients

Abstract: Background: Changes in regional neural activity and functional connectivity in cervical spondylotic myelopathy (CSM) patients have been reported. However, resting-state cerebral blood flow (CBF) changes and coupling between CBF and functional connectivity in CSM patients are largely unknown.Methods: Twenty-seven CSM patients and 24 sex/age-matched healthy participants underwent resting-state functional MRI and arterial spin labeling imaging to compare functional connectivity strength (FCS) and CBF between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
0
4
0
1
Order By: Relevance
“…1 ). 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65
Fig. 1 PRISMA flow diagram of study selection .
…”
Section: Resultsunclassified
See 3 more Smart Citations
“…1 ). 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65
Fig. 1 PRISMA flow diagram of study selection .
…”
Section: Resultsunclassified
“…A total of 36 studies explored functional changes in 1200 patients with DCM before surgical intervention ( Supplementary Data 6 ). Of these, 19 assessed FC, 21 , 23 , 24 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 nine assessed activation/VOA, 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 eight assessed ALFF, 21 , 39 , 44 , 55 , 56 , 57 , 58 , 59 five utilised graph theory analysis, 30 , 40 , 41 , 60 , 61 three assessed BOLD signal changes, 30 , 47 , 50 and three assessed ReHo. 21 , 39 , 62 Functional changes in anatomical brain regions of 73% (871/1200) of patients with DCM were compared against HCs and mapped onto the Desikan-Killiany atlas ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reported that gFCD is a key biomarker for various diseases ( 45 ). Although previous studies reported the aberrations in GMV and gFCD as important characteristics of DCM ( 18 , 46 , 47 ), the associations between the spatial distribution patterns of GMV and gFCD alterations remain unexplored.…”
Section: Introductionmentioning
confidence: 99%